Financial investigation and forensic accounting - Manning, George A. (Boca Raton, FL : Taylor & Francis Group, 2005)
This book offers a thorough examination of current methods and legal concerns for the detection and prosecution of economic crime.
Includes bibliographical references (p. 551-553) and index.
aug 04/06/13
Loans
Keywords: White collar crime investigation -- United States; Forensic accounting -- United States; Fraud investigation -- United States